Evaluasi Program Penguatan Karakter: Studi pada Sekolah Non-Piloting PPK di Kota Malang - Fuad Jaya Miharja; Adi Slamet Kusumawardana; Arif Setiawan (Universitas Negeri Medan, 2020)
The program for strengthening character education is only carried out in several pilot schools so that there is not much information available to what extent character education has actually been carried out in other schools, especially in non-piloting schools. This study aimed to measure the feasibility of strengthening character education in non-piloting schools. The population in this quantitative descriptive study was teachers at junior high school in Malang. The sampling technique used was purposive sampling. The subjects involved in this study were six teachers of Junior High Schools 20 of Malang, Junior High Schools 27 of Malang, and Muhammadiyah 1 Junior High School. Data collection used questionnaires and analysed descriptively statistically. The results of the study showed that the three schools have implemented character strengthening programs seen from the ten assessment components i.e. pre-assesment, programme socialization, vision, programme design, class-based implementing, school culture strengthening, social partisipation, core value implementing, and evaluation. These results indicated that character strengthening has become a positive habit but not yet optimal. The results of this study can be used as a basis for identifying appropriate follow-up steps for improving achievement of character strengthening in schools.